Branchial cyst of the second pharyngeal pouch: case report in a 2-year-old patient - Ayquipa-Arrospide, Tula Dariela (2024)
Introduction: Branchial arch malformations originate from the incomplete obliteration of the clefts and pouches in embryological development, constituting the second cause of congenital head and neck mass in pediatric ages. Case of report: The clinical presentation depends on the branchial arch involved. We present the case of a 2-year-old boy who presented frequent episodes of stridor and intermittent fever since 6 months after birth. Computed tomography showed a cystic-looking lesion located in the right pharyngeal mucosal space with extension to the oropharynx. The lesion was resected by a transoral endoscopic approach. The pathological report was compatible with a branchial cyst of the second pharyngeal pouch. Conclusion: The diagnostic suspicion of congenital branchial malformations and their correct identification are essential for timely treatment in pediatric ages.